Monitoring of the Wild Boar (Sus Scrofa Linnaeus, 1758), Distributed in the Territory Of Karakalpakstan (Texas Journal of Agriculture and Biological Sciences, 2024)
This article presents monitoring of the distribution of the wild boar population in Karakalpakstan. As a result of research work, it was established that wild boars are widespread in the Lower Amu Darya delta, around natural lakes and artesian wells in the north-west of the Kyzylkum, as well as in areas between the cracks of the Northern Ustyurt plateau and the Aral Sea